MATERNAL AND FETAL OUTCOMES IN HELLP SYNDROME AT 23 WEEKS GESTATION: SYSTEMATIC REVIEW - Aldela Paramerta, I Made Elga (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Hypertensive disorders, affecting 5-10 of pregnancies, are a leading cause of maternal and perinatal mortality. Preeclampsia-eclampsia, a syndrome contributing to significant global deaths, demands prompt identification and management, particularly in resource-limited settings. Detecting and addressing early and late-onset preeclampsia are crucial for maternal and neonatal well-being. HELLP syndrome, a severe complication of preeclampsia, presents diverse symptoms and risks, with a maternal mortality rate as high as 24 Understanding its outcomes in pregnancies before 23 weeks is essential to guide better management strategies for improved maternal and neonatal health in such critical cases. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 15 results. After looking at the titles and summaries, we found 6 papers that fit our criteria. At first, we excluded one articles because they were written in a review style. But after reading the full papers carefully, we included four papers in our final analysis. These papers included a retrospective observational study and several case reports. Conclusion: Occurrences of HELLP syndrome without associated hypertensive disorders and recurrent intrahepatic ruptures at extremely premature gestational ages are rare but pose significant risks to mothers and newborns. Swift diagnosis, pregnancy termination, and continuous monitoring are crucial to address early-onset HELLP syndrome, emphasizing the need for immediate attention and prompt management.